Cytochemical and ultrastructural observations of anthers and pollen grains in Lathyrus undulatus Boiss - VARDAR, FİLİZ (UNIV ZAGREB, FAC SCIENCE, DIV BIOLOGY, 2011)
In Lathyrus undulatus Boiss. (Fabaceae), the young microspore stage of anther development was characterized by the enlarged secretory tapetal cells, which presented an intense reaction with regard to protein, insoluble polysaccharides and lipids. At bicellular pollen stage, the middle layer and the tapetum degenerated. After degradation of the tapetum, epidermis and single row U-shaped endothecium existed in the mature anther wall, and pollen grains remained in the locus. Young microspores had a spherical and centrally located nucleus with one or two nucleoli, many spherical lipid bodies and starchy plastids. A mature pollen grain contains insoluble polysaccharides, proteins, lipids and calcium. The mature pollen had the following morphological characteristics: 3-zono-colporate, prolate, tectate (imperforate) type of exine and perforate type of structure. The intine formed an important constituent portion of the wall, and consisted two sublayers: an outer intine (exintine) and an inner intine (endintine). The well-defined exine was made up of lipoidal substances and protein, but the intine composed of insoluble polysaccharides and protein. The bicellular state of the pollen grains persisted to anthesis.
Keywords: Anther; cytochemistry; Fabaceae; Lathyrus undulatus; microsporogenesis; pollen; SEM; TEM; tapetum; PROGRAMMED-CELL-DEATH; MICROSPOROGENESIS; FABACEAE; CALCIUM; TAPETUM; SURFACE; TURKEY